(3Md GdTHgI GdeTghQI HGdLPQ GdCUes - (3eMeO GdLaQj , eMeO GdLaQj,J (B1186 (3g` s
(3ChdgG (B:s
(3bO CLGH GdMVQI GdLdGdjI GdeMeOjI HCf bhd GdbGFd cd cdGe ai gPg GdSGYI cGPH s
(3BNQgG (B:s
(3aGf UGQ gPG GdLhGH ebHhdkG YfO GdYdeGA UGQ MbjbjkG JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdMGOi YTQs
(3GfXQg eY GdeNWhW Qbe (B292s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B158s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs